Research on the Cultivation Path of Teaching Ability in Higher Vocational Primary Education under the Integration of "Post, Course, Competition, Certificate" —— A Case Study of Liaoning Province (Journal of educational development exploration, 2026)
The integration of "post, course, competition, certificate" is an important direction for innovation in vocational education talent cultivation. This study takes higher vocational colleges in Liaoning Province offering primary education majors as the research object. It analyzes problems such as the disconnect between curriculum and job requirements, and proposes forming a virtuous cycle of "setting courses based on posts, promoting teaching through competitions, and validating learning with certificates" to cultivate high-quality primary school teachers for basic education.
Keywords: Integration of post, Course, competition, certificate; Higher vocational education; Primary education; Teaching ability cultivation; Liaoning province